Method of Assessing Fatigue Hazard to Steel Railway Bridges - Wysokowski, A. (Engineering Transactions, 2001)
This research has been carried out as part of the ministerial R &; D program: "Improvement of the condition of roads and highway and railway bridges". This paper deals with the establishment of guidelines relating to "Checking the fatigue hazard to railway bridges". Its aim is to provide a relatively simple and coherent method of assessing the fatigue hazard to steel structural elements in both newly designed bridges and those being in service under different conditions of traffic on Polish Railways lines. This is proposed to be done on the basis of the latest results of fatigue studies. Another aim is to develop a method of assessing the allowable – from the point of view of fatigue – the service life of railway bridges in service. Finally, examples of checking the fatigue hazard to structural elements of railway bridges by means of the proposed method are given.